Iran's Health System Performance in Achieving Goals Based on the World Health Organization's Framework: A Scoping Review - Reza Negarandeh; Aziz Kamran; Heshmatolah Heydari (Gonabad University of Medical Sciences, 2022)
Background: The health system of each country are required to achieve the goals based on appropriate frameworks. Assessment of health system performance provides an opportunity to address the main mission through recognizing new needs and resolving existing gaps. This review study aims to investigate Iran's health system performance in achieving its goals based on the World Health Organization (WHO)'s conceptual framework.  Methods: This scoping review was conducted based on Arksey and O'Malley's methodological framework. A search in international databases including Web of Science, Scopus, PubMed/Medline and in national databases such as SID, MagIran and IranDoc was conducted using the keywords "health system, Iran", "disease burden", "responsiveness" and "financial contribution", which were used in both English and Persian separately for each variables of health promotion, responsiveness, and fair financial contribution. Retrieved articles were analyzed using qualitative synthesis method.  Results: Data extracted from articles categorized into the three groups of "Health" (with sub-categories of epidemiologic and demographic transitions), "Responsiveness" and "Fair financing and financial risk protection". Synthesis of data revealed that the profiles of diseases has been changed over recent decades in Iran, which has resulted in epidemiologic and demographic transitions. In terms of responsiveness, services provided by the health system had not fulfilled patients' expectations. Regarding fair financial contribution, synthesis of data showed that people had faced high health costs, with a high amount of out-of-pocket payment. Conclusion: Iran's health system has not yet achieved the goals recommended by the World Health Organization. Fundamental reforming is required in the health system of this country.